STUDY OF PSYCHOLOGICAL IMPACT OF ASSESSMENT OF PROFESSIONAL QUALITIES OF PERSONNEL (ON THE EXAMPLE OF THE BANK) - Hovhannisyan, S.V.; Khonchanchyan , M. A. (Modern Psychology, 2020)
Organizations' development trends provide new requirements for HRM professionals in the changing and competitive environment of today. In order to fully implement human resources management functions, HRM specialists have adopted a policy of professional assessment for employees. The issue of effective integration of the assessment system in HR management process is becoming extremely urgent in present, since staff motivation, effective communication and satisfaction level in the organization greatly depends on the competent approach to employee appraisal and rational operation,. So, this article is directed to the research of the issues related to the appraisal and integration of staff assessment in the HRM system, as well as the peculiarities of the assessment of the staff's professional qualities on employee motivation and satisfaction with work.
Keywords: Human Resource Management; staff; appraisal of professional qualities; motivation; job satisfaction